BONUS DEMOGRAFI: PERAN LINGKUNGAN KELUARGA UNTUK PENGOPTIMALAN JUMLAH WIRAUSAHAWAN DI MASA DEPAN - Muhammad Tafdhil Amanda,; Myrtana Pusparisti,; Yohanes Wien Tineka,; Deswita Auraliyani Fatolah Putri, (Juremi: Jurnal Riset Ekonomi, 2024)
This study is motivated by the demographic bonus phenomenon both in terms of benefits and threats in the future. Increasing the number of entrepreneurs in the future is one way to take advantage of the demographic bonus because at least it will open up many opportunities to become a producing country and reduce unemployment. Focusing on entrepreneurial intentions, this research examines one of the factors that can influence it from an early age, namely the family environment. Quantitative sampling methods were used with students majoring in business, and provided assumptions of validity and reliability. The research results show that there is a significant positive impact between the family environment and entrepreneurial intentions, which also implies that to take advantage of the demographic boom phenomenon by creating many entrepreneurs in the future, encouragement and education can be targeted at the family environment from an early age